2014
DOI: 10.1021/jp4076355
|View full text |Cite
|
Sign up to set email alerts
|

Structures and Phase Transition of a MoS2 Monolayer

Abstract: As an inorganic cousin of graphene, MoS2 monolayer has attracted considerable attention. However, a full understanding of its structure and stability is still lacking due to its dependence on experimental synthesis conditions. Using first-principle calculations combined with Boltzmann transport equation, we have extensively studied the geometry, energetics, electronic structure, optical absorption, and carrier mobility of various phases of MoS2. We have not only identified the stable phases of a MoS2 monolayer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

48
402
1
4

Year Published

2014
2014
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 459 publications
(463 citation statements)
references
References 50 publications
(67 reference statements)
48
402
1
4
Order By: Relevance
“…It is believed to be quite distorted compared to that of 2H-MoS 2 , which could cause it to be very reactive. [15,32] Given our poor understanding of the structure of 1T-MoS 2 it is not yet possible to definitively explain why and how it reacts with electrophiles.…”
Section: And Co-workers Later Took Advantage Of This Functionalizamentioning
confidence: 99%
“…It is believed to be quite distorted compared to that of 2H-MoS 2 , which could cause it to be very reactive. [15,32] Given our poor understanding of the structure of 1T-MoS 2 it is not yet possible to definitively explain why and how it reacts with electrophiles.…”
Section: And Co-workers Later Took Advantage Of This Functionalizamentioning
confidence: 99%
“…While the studies on the yield stress in SLMoS 2 are limited, the novel structure transition in SLMoS 2 has received considerable attention [70][71][72][73]. In this structure transition, the outer two S atomic layers are shifted relative to each other, leading to abrupt changes in the electronic and phonon properties in SLMoS 2 .…”
Section: Mechanical Propertiesmentioning
confidence: 99%
“…Within the GGA-PBE level, the calculated band gap of 2H MoS 2 is 1.66 eV and more stable than 1T MoS 2 with total energy 0.85 eV, which are consistent with the previous report. 12 By gliding only one S plane of MoS 2 to the center of the hexagonal, semiconducting 2H phase will gradually transit to metallic 1T phase. Fig.2 clearly displayed the transition energy barrier (1.04 eV) in monolayer MoS 2 from the metastable 1T phase to the stable 2H phase.…”
Section: A Structural and Thermodynamically Stabilitymentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8] Depending on the arrangement of its S atoms, monolayer MoS 2 appears in many distinct phases, two of them are more popular and exhibits substantially different electronic structures: 2H (trigonal prismatic, D 3h ) MoS 2 is a semiconductor with a finite band gap between the filled d z 2 and empty d x 2 − d y 2 ,xy bands, and 1T (octahedral geometry, O h ) phase is metallic with Fermi level lying in the middle of degenerate d xy,yz,xz single band. 9 It has been recently demonstrated that the reversible transition from 2H to 1 T phase can be achieved in monolayer MoS 2 by annealing, 10 electric doping, 11,12 applying strain 13 or electron-beam irradiating. 14 More importantly, a mixed phase (2H and 1T) structure with the abrupt phase interface and matched lattice has been demonstrated experimentally.…”
Section: Introductionmentioning
confidence: 99%